Nocardia brasiliensis Induces Formation of Foamy Macrophages and Dendritic Cells In Vitro and In Vivo - Coers, Jörn; Meester, Irene; Rosas Taraco, Adrián Geovanni; Salinas Carmona, Mario César (Public Library of Science, 2014)
Foamy cells have been described in various infectious diseases, for example in actinomycetoma induced by Nocardia brasiliensis. These cells are generally considered to be macrophages, although they present dendritic cell (DC)-specific surface markers. In this study, we determined and confirmed the lineage of possible precursors of foamy cells in vitro and in vivo using an experimental actinomycetoma model in BALB/c mice. Bone marrow-derived macrophages (BMDM) or DC (BMDC) were infected in vitro with N. brasiliensis or labeled with carboxyfluorescein diacetate succinimidyl ester (CFSE). Both, macrophages and DC, differentiated into foamy cells after in vitro infection. CFSE-labeled BMDM or BMDC were tested for phagocytosis and CD11c/CD11b receptors markers expression before being transferred into the actinomycetoma lesion site of infected mice. In vivo studies showed that BMDM and BMDC were traced at the site where foamy cells are present in the experimental actinomycetoma. Interestingly, many of the transferred BMDM and BMDC were stained with the lipiddroplet fluorophore Nile Red. In conclusion, macrophages and DC cells can be differentiated into foamy cells in vitro and in vivo during N. brasiliensis infection.